Ethnic and Gender Wage Disparities in Sri Lanka - Ajwad, Mohamed Ihsan; Kurukulasuriya, Pradeep (World Bank, Washington, D.C., 2013)
The authors examine wage inequalities in Sri Lanka's formal sector using data from the Sri Lanka Integrated Survey 1999-2000. The study aims to: a) investigate whether the labor market is characterized by wage disparities among ethnic and gender groups; b) identify the determinants of wages and the factors that affect the wage differential; c) analyze the determinants of wages across the conditional wage distribution; and d) disaggregate the ethnic or gender wage disparities where observed into a component affected by the endowment of productive characteristics, as well as a component affected by the returns to those productive characteristics in the labor market. The authors find that ethnicity is not a significant determinant of wages. The result is robust to different specifications. In addition, ethnicity is not significant in any of the emotional quantiles estimated. However, there is gender disparity in wage rates in Sri Lanka. The magnitude of this disparity varies depending on the worker's ethnicity. This gender wage disparity varies by about 10 percent for Tamils and 48 percent among other ethnicities. In addition, the authors find that much of the gender disparity is not explained by productive characteristics, implying that discrimination against women may play a role. The quantile regression estimates indicate that the premium paid to male workers in the labor force is more pronounced in the upper conditional wage rate distribution.